Intervenção implementada por profissional e cuidador a crianças com TEA - OLIVEIRA, Juliana Sequeira Cesar de (Universidade Federal do Pará, 2019)
Applied Behavior Analysis (ABA) has been shown to be effective in intervention for people with autism. In Brazil, analytical-behavioral services are not accessible to a large portion of the population, which does not have the financial means to afford high intervention costs. More accessible intervention can be through by caregivers teaching. There is a considerable amount of studies in the international and national literature showing that parents may be able to apply teaching accuracy to children with autism. In this sense, a question arises: how comparable is the result of intervention implemented by caregivers and professionals? Thus, the objective of the present study was to compare the application of the caregiver application in relation to the application by professionals in training with children with autism. Three children with autism, their caregivers and five professionals participated in the study. The sessions happened at UFPA and at the children's home. The experimental design used was the use of multiple probes between teaching programs with alternation between treatments (implementation by caregivers and by professionals). The dependent variable was the percentage of accuracy of performance of the child in each teaching program. The results show no critical difference between caregiver and professional implementation. An average number of attempts for Lucila to archive criterion in the teaching programs was 78 trials (professional) and 58 trials (caregiver), with a standard deviation of 11.3 and 18.7 respectively. An average number of trials for which Lucas to archive the criteria of 49.9 trials (professional) and 58.8 (caregiver), with the standard of 19.9 for both interventions. For Daniel, the intervention was interrupted to start a specific training of inappropriate behavior management for the caregivers. The results of this study are the beginning of a major research line on ABA concerning to autism and it suggests that caregiver implementation can be as efficient as the professional implementation.